2012
DOI: 10.1590/s1516-80342012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre as palavras eliciadas na Avaliação Fonológica da Criança e as variáveis idade, gênero e gravidade do desvio fonológico

Abstract: Relationship between words elicited in the Childrengender, and severity level of PD. The target-words produced more frequently were those referring to names of objects belonging to the daily routine of children, unlike substitutions, which were more frequent when the target-word corresponded to objects visually unknown to the children. Conclusion: The production of the words belonging in the CPA is influenced by age, gender and severity level of phonological disorders. It is essential that the words selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Tanto na avaliação, quanto na reavaliação das crianças, as substituições ou não reconhecimento das figuras foram percebidos. Algumas substituições foram descritas na literatura 19 .…”
Section: Discussionunclassified
“…Tanto na avaliação, quanto na reavaliação das crianças, as substituições ou não reconhecimento das figuras foram percebidos. Algumas substituições foram descritas na literatura 19 .…”
Section: Discussionunclassified
“…By only hearing the disordered productions, it is started to think about the acquisition complexity. Several researches (2,(3)(4)(5)6,(7)(8)(9)(10)(11)(12)(13) have been performed, related to typical and atypical phonological acquisition, and, to analyze that production complexity in the evaluated population, it is important to use proper evaluation instruments, validated and standardized.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical practice, it is observed that children have presented difficulties in the elicitation of some pictures, because they do not have contact with the target, or because it is difficult for them to access the name, what makes the researchers believe that the used pictures should be updated. It is possible to quote some examples of their difficulty in the words "radio", "globe", "disk", "zoological", "circus", "elephant", "antenna", "church", "couch", "shelf", "tile", "anchor", etc (3) .…”
Section: Introductionmentioning
confidence: 99%